Estrategias metodológicas y su relación en los resultados de aprendizajes significativos, en el área de lengua y literatura en los estudiantes de quinto y sexto grados de educación general básica de la unidad educativa Marista de la ciudad de Catacocha, período lectivo 2014-2015 - Guamán Vega, María Guadalupe (2014)
The present investigation realized about the problematic of methodological strategies and significant learning, it was planted as general objective analyze methodological strategies used by docents of Educative Unit Marista, with finality to determine the relation in acquisition of significant languages on the language and literature area, of students from fifth and sixth general basic education years, to improve the docent practice in this subject, and as specific objectives, establish the existent relation between the methodological strategies utilized by teachers and the results of significant learning and elaborate methodological guide directed to the docents of the language and literature area that contains different methodological strategies to obtain better results of significant learning in the students of fifth and sixth general basic education years, the methodology utilized was sustained on the scientific method and as particular methods were used inductive-deductive, analytic-synthetic and descriptive, applying survey technique to recollection of field information of a population compound of two docents and one hundred fifteen students. Once the information was processed it was concluded that the methodological strategies applied by the docents were lecture and underlining of principal ideas, interspersed questions, summaries, participation of the students, team work, strategies of learning listening with attention and participate actively in classes and the most developed skills by students in language and literature area were understanding texts and reading; the principal conclusion was that methodological strategies utilized by the docents in teaching learning process from language and literature area has is directly related with the achievement of significant learning of the students. Concluded the investigative process was planted as an alternative alignment a didactical guide of methodological strategies to achieve significant learning.